Jurisprudence Analysis Of Ma Verdict No 557/Pdt/2016/Pt.Dki On The Malaysian Ambassador's Land Title Dispute - Puspitasari Wardoyo, Nanda; Arum Prastyanti, Rina (Mutiara: Multidiciplinary Scientifict Journal, 2024)
This research analyzes Supreme Court Decision No. 557/PDT/2016/PT.DKI regarding a land title dispute involving the Government of Malaysia and a number of parties in Indonesia. The dispute stems from a claim over land used as the official residence of the Malaysian Ambassador, which had previously been purchased under a notarial deed in 1971. This study aims to understand the application of law in dispute resolution, as well as the legal implications of this decision for the development of jurisprudence and land law practice in Indonesia. The method used is jurisprudential analysis, focusing on the legal documents and arguments presented during the trial. The results of the analysis show that this decision affirms the importance of legal protection for foreign embassies in accordance with the 1961 Vienna Convention, as well as providing clear guidelines in the settlement of land disputes. The research also found that low public awareness regarding legal land ownership is a major factor in the emergence of disputes. In addition, this study suggests the need to improve the mediation mechanism at the BPN and socialization regarding legal land ownership to reduce future disputes. As such, this research is expected to contribute to a deeper understanding of land law and improve legal certainty in Indonesia, as well as provide practical recommendations for policymakers in managing land disputes.